FRI0281 Predictors of Quality of Life in Behçet's Syndrome. (9th June 2015) - Bozcan, S.; Ozguler, Y.; Saygin, C.; Uzunaslan, D.; Tascilar, K.; Ugurlu, S.; Hatemi, G.
Abstract : Background: Quality of life is commonly impaired in patients with chronic inflammatory diseases. The disease itself as well as the drugs used may be responsible for this impairment. Behçet's syndrome (BS) is a multisystem vasculitis with a wide variety of manifestations including oral ulcers, genital ulcers, nodular lesions, papulopustular lesions, arthritis, uveitis, venous thrombosis, arterial aneurysms, neurologic and gastrointestinal involvement. Determining the factors affecting quality of life in BS patients, would help developing effective management strategies. Objectives: We aimed to determine the factors that impair quality of life (QoL) in BS. Methods: Short- Form 36 (SF-36) physical component score (PCS) and mental component score (MCS) and Behçet Disease Quality of Life (BDQoL) questionnaires were filled by consecutive BS patients attending our outpatient clinic. Socioeconomic factors, each type of organ involvement during the disease course, during the last 4 weeks, disabilities caused by each, treatment modalities and overall disease activity were tested with regression analysis as possible determinants of QoL. Results: 453 patients (M/F: 240/213, mean age: 38.2±10.8) were included in our study. 223 patients had eye involvement, 94 patients had vascular involvement, 102 patients had joint involvement, 28 patients had neurologic involvement, 2 patients had gastrointestinal involvement and 127 patients had only mucocutaneous involvement without organ involvement. Determinants of BDQoL in the whole group were BSAS, household income, perceived sufficiency income, neurologic damage, mucocutaneous involvement (R 2 : 0.38, p<0.001), among women were BSAS, neurologic and mucocutaneous involvement (R 2 : 0.36, p<0.001), and among men were disease related working disability, BSAS, household income, joint attack during the last 4 week, vascular and neurologic damage (R 2 : 0.39, p<0.001) Determinants of PCS in the whole group were BSAS, household income, eye, vascular and joint involvement during the last 4 week, disease related working disability (R 2 : 0.31, p<0.001), among men were BSAS, disease related working disability, household income, vascular involvement, vascular and joint involvement during the last 4 week (R 2 : 0.32, p<0.001), among women were BSAS, mucocutaneous involvement and perceived sufficiency income (R 2 : 0.32, p<0.001). Determinants of MCS in the whole group were BSAS, household income, neurologic damage (R 2 : 0.20, p<0.001), among men were BSAS, household income, neurologic damage, disease related working disability, mucocutaneous involvement (R 2 : 0.26, p<0.001), among women were BSAS and mucocutaneous involvement (R 2 : 0.21, p<0.001). Conclusions: In addition to overall disease activity in women mucocutaneous and neurologic involvement and in men neurologic and vascular damage and joint attack seem to impair quality of life in BS. Determining the factors predicting the quality of life are important for developing management strategies and also may help determining the items that need to be addressed while developing outcome measures. Disclosure of Interest: None declared